IGF-1 Deficiency Promotes Pathological Remodeling of Cerebral Arteries: A Potential Mechanism Contributing to the Pathogenesis of Intracerebral Hemorrhages in Aging. (21st June 2018) - Fulop, Gabor A; Ramirez-Perez, Francisco I; Kiss, Tamas; Tarantini, Stefano; Valcarcel Ares, Marta Noa; Toth, Peter; Yabluchanskiy, Andriy; Conley, Shannon M; Ballabh, Praveen; Martinez-Lemus, Luis A; Ungvari, Zoltan; Csiszar, Anna
Abstract: Clinical and experimental studies show that age-related decline in circulating insulin-like growth factor-1 (IGF-1) levels promotes the pathogenesis of intracerebral hemorrhages, which critically contribute to the development of vascular cognitive impairment and disability in older adults. Yet, the mechanisms by which IGF-1 deficiency compromises structural integrity of the cerebral vasculature are not completely understood. To determine the role of IGF-1 deficiency in pathological remodeling of middle cerebral arteries (MCAs), we compared alterations in vascular mechanics, morphology, and remodeling-related gene expression profile in mice with liver-specific knockdown of IGF-1 ( Igf1 f/f + TBG-Cre-AAV8) and control mice with or without hypertension induced by angiotensin-II treatment. We found that IGF-1 deficiency resulted in thinning of the media and decreased wall-to-lumen ratio in MCAs. MCAs of control mice exhibited structural adaptation to hypertension, manifested as a significant increase in wall thickness, vascular smooth muscle cell (VSMC) hypertrophy, decreased internal diameter and up-regulation of extracellular matrix (ECM)-related genes. IGF-1 deficiency impaired hypertension-induced adaptive media hypertrophy and dysregulated ECM remodeling, decreasing elastin content and attenuating adaptive changes in ECM-related gene expression. Thus, circulating IGF-1 plays a critical role in maintenance of the structural integrity of cerebral arteries. Alterations of VSMC phenotype and pathological remodeling of the arterial wall associated with age-related IGF-1 deficiency have important translational relevance for the pathogenesis of intracerebral hemorrhages and vascular cognitive impairment in elderly hypertensive patients.